TRANSFORMATION OF PROFESSIONS IN THE DIGITAL ECONOMY, MOST IN DEMAND IN THE LABOR MARKET OF UZBEKISTAN - ABDUKARIMOV BARAT-ALI ABDUKARIMOVICH; MIRZAEVA SHIRIN NODIROVNA (Research Parks Publishers, 2023)
The article assesses the relevance of the vocational education and training system in terms of the requirements of the labor market. Of practical interest is the study and use of foreign approaches to the creation of a labor market forecasting system, consisting of the balance of labor resources and the economy's need for personnel in the context of vocational and qualification groups of workers in Uzbekistan. Vocational education and training in Uzbekistan does not have the skills that businesses need to be successful. The measures currently being taken to introduce effective mechanisms to strengthen interaction between vocational educational institutions, vocational training centers and employers in Uzbekistan will serve to train qualified personnel in vocational educational institutions, taking into account the needs of employers and the demand of sectors of the economy.